Les apories identitaires de la « deuxième génération d’Albanais » en Grèce au prisme de Xénia (Panos Koutras, 2014) - Hugues Simonin (Cahiers Balkaniques)
An experience of migration in Greece has been largely ignored. It is the experience of children born there from immigrants, legal or not, during the 1990’s, who then got raised in Greece, but who must prove when they turn 18 that at least one of their parents has Greek citizenship, in order to get theirs. In his movie Xenia, Koutras tells this complex experience through the case of two brothers. They are “second generation Albanians” searching for a father and a fatherland in contemporary Greece. My goal is to show how cinematographically, the director handles the identity aporias that the protagonists face due to their strange strangeness. From the brothers’ experience, he elaborates a representation of a relation to oneself and the others that is unstable and partly alienated in terms of social and psychological conventions. He goes even further. Their experience of becoming orphans and stateless morphs into an identity reappropriation that twists and subverts the very core of the traditional meaning of “identity”. More precisely, to film the transformation of these aporetical constraints into resources, the director uses a combination of formal and narrative processes rooted in the queer set of representations and actions, that he also contributes to extend.